Diffuse Pulmonary Lymphangiomatosis - Kunal C Kadakia; Sandeep M Patel; Eunhee S Yi; Andrew H Limper (Canadian Respiratory Journal)
Diffuse pulmonary lymphangiomatosis (DPL) is a rare disease characterized by infiltration of the lung, pleura and mediastinum with thin-walled lymphangiomas. DPL can result in mass effect from infiltrative disease, restrictive and obstructive pulmonary physiology, chylous effusions and respiratory failure. The present article discusses clinical, radiographic and pathological features, and treatment options for DPL.